Early detection of cardiotoxicity by 3D speckle tracking imaging of area strain in breast cancer patients receiving chemotherapy. Issue 9 (10th September 2019) - Chen, Jianqiong; Wang, Ling; Wu, Fang‐Fang; Sun, Guoping
Abstract: Eighty‐three breast cancer patients who underwent six cycles of EC chemotherapy regimen (epirubicin + cyclophosphamide) without symptoms and signs of heart disease were enrolled in the study. Three‐dimensional speckle tracking imaging technique (3D‐STI) was used to measure left ventricular global area strain (GAS), overall annular strain (GCS), overall longitudinal strain (GLS), and overall radial strain (GRS). Meanwhile, serum troponin T (Hs‐cTnT) was measured. The clinical value of each index on cardiotoxicity after chemotherapy was analyzed using the receiver operating characteristic (ROC) curve. Hs‐cTnT increased from the early stage to the end during chemotherapy, but it was still in the normal range. During the mid‐chemotherapy and the end‐chemotherapy, GAS, GLS, GCS, and E/A significantly reduced, while the changes in LVESV, LVEDV, LVEF, and GRS were not significant after chemotherapy. Pearson correlation analysis showed a significant negative correlation between GAS and anthracycline doses ( r  = −.772, P  < .01); GAS and Hs‐cTnT were significantly negatively correlated ( P  < .05). The area under the curve (AUC) of GAS, GLS, GCS, and GRS are 0.815, 0.683, 0.645, and 0.585, respectively. A GAS of −31.5% was used as the cutoff value for diagnosing left ventricular systolic dysfunction after receiving chemotherapy. The sensitivity of the previous parameters was 81.9%, and the specificity was 80.3%. Interobserver consistency analysis showed that 3D‐STI strain parameter measurement has good repeatability. GAS has greater value in predicting early myocardial damage after anthracycline chemotherapy.